Safety of Topical Mitomycin C after Keloid Excision: A Pilot Study. (2nd September 2014) - Teti, Virginia P.; Liu, Michelle F.; Lim, Alan A.; Cilento, Benjamin W.; Gallagher, Thomas Q.
Abstract : Objectives: (1) Ascertain the safety of topical mitomycin C in the prevention of recurrent keloid scars after surgical excision. (2) Determine the efficacy of mitomycin C in keloid prevention. Methods: This was a prospective pilot study of 10 patients. Between August 2009 and September 2011, subjects underwent surgical excision of keloids located in the head and neck region with a one‐time, intraoperative, topical application of mitomycin C. Patients were followed for 12 months postoperatively. During this period, laboratory values reflecting complete metabolic profile and coagulation studies were drawn preoperatively and postoperatively (at 2 weeks and the first, second, and third months). Additionally, photo‐documentation was obtained at regular intervals to ascertain the efficacy in prevention of keloid recurrence. Results: Twelve patients enrolled in the study. Nine patients completed the protocol. Three patients dis‐enrolled prior to surgical excision. No patients were lost to follow‐up. Analysis of variance performed demonstrating no statistical significance in the variance of the laboratory values. Additionally, no patient demonstrated abnormality of any laboratory value beyond the reference range. Next, clinical examination of the wounds demonstrated no evidence of necrosis or dehiscence. Finally, no wound demonstrated recurrence at the one‐year follow‐up visit. Conclusions: Mitomycin C appears safe for topical use after excision of keloids in the head and neck region. This study demonstrates no evidence of recurrence in all patients enrolled and followed for one year.